G400(P) Two cases of mild encephalopathy with a reversible splenial lesion (MERS). (24th May 2017) - Awad, A; Avula, S; DeGoede, C; Nair, P; Rakshi, K; Iyer, A; Kneen, R
Abstract : Introduction: Mild Encephalopathy with Reversible Splenial lesion (MERS) is a newly-proposed clinical-radiological para/post infectious syndrome characterised by an acute, transient encephalopathy and radiological evidence of a reversible lesion in the splenium of the corpus callosum (SCC) with a good prognosis. We describe two cases of MERS in two UK teaching hospitals. Methods: Case note review. Results: Case 1, a 13 year old African-Caribbean boy and Case 2, an 11 year old Caucasian girl with a diagnosis of ulcerative colitis treated with mercaptopurine [0.75 ml once daily (OD)] and mesalazine (1500 mg OD) presented with encephalopathy, headache, ataxia, and pseudobulbar features. Case 1 was febrile. Case 2 had an afebrile prodrome with sore throat, vomiting and diarrhoea (5 days). Both were treated with aciclovir and cefotaxime. Case 1 received clarithromycin. Both had an LP: the only abnormality being 10 white cells in the cerebrospinal fluid of case 1. Viral PCRs were negative. The MRI for case 1 revealed abnormal signal on T2/FLAIR and diffusion weighted imaging in the SCC with no gadolinium enhancement. Case 2 had similar findings and abnormal signal on T2/FLAIR in the cerebellar hemispheres. Both received a course of intravenous methylprednisolone, 1g OD, for 3 and 5 days respectively. Case 1 had evidence of a recent Mycoplasma pneumoniae infection (serum IgM antibody titre 1/640). He made a full recovery and MRI imaging findings resolved (2 week admission). Case 2 still had left upper limb dyspraxia and mild cognitive problems 5 weeks after onset of symptoms. Conclusion: Approximately 200 MERS cases have been reported since 2004 in association with bacterial, fungal, and viral illnesses – particularly influenza.The pathogenesis remains unclear, but inflammatory cytokine-mediated intramyelinic oedema has been suggested as a putative mechanism. The majority of cases make a full recovery within one week and all within one month. These two cases add to the number of cases of MERS reported outside of East Asia, and highlight MERS as a differential for para or post-infectious encephalopathy. Our case with an incomplete recovery also adds to the phenotype and if additional imaging changes are present, the prognosis may need to be more guarded.